2011
DOI: 10.1007/s11442-011-0844-7
|View full text |Cite
|
Sign up to set email alerts
|

Community-based scenario modelling and disaster risk assessment of urban rainstorm waterlogging

Abstract: Scenario modelling and the risk assessment of natural disasters is one of the hotspots in disaster research. However, up until now, urban natural disaster risk assessments lack common procedures and programmes. This paper selects rainstorm waterlogging as a disaster to research, which is one of the most frequently occurring hazards for most cities in China. As an example, we used a small-scale integrated methodology to assess risks relating to rainstorm waterlogging hazards in the Jing'an District of Shanghai.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 13 publications
0
87
0
Order By: Relevance
“…Although several urban rainfallrunoff models have been developed in China since the 1990s, their intrinsic shortcomings, such as poor availability of the models themselves, makes it difficult to apply them in different urban environments Wang et al 2011a). Combined with the distributed hydrologic model, the GIS-based 'water balance' method, which assumes the volume of waterlogging is equivalent to total runoff, has usually been used as a simplified way to determine the maximum inundation extent and depth for small and enclosed urban areas such as Longhu District of Shantou city, Longwan District of Wenzhou city, Jing'an District of Shanghai city and Tianjin Binhai New Area (Zhang 1995;Zhao et al 2004Zhao et al , 2010Yin et al 2011c;Hu et al 2012). Based on field survey, GIS point interpolation methods have occasionally been used to obtain the inundation extent and depth for some urban communities (Yin et al 2009;Li et al 2014).…”
Section: Urban Flood Hazard Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Although several urban rainfallrunoff models have been developed in China since the 1990s, their intrinsic shortcomings, such as poor availability of the models themselves, makes it difficult to apply them in different urban environments Wang et al 2011a). Combined with the distributed hydrologic model, the GIS-based 'water balance' method, which assumes the volume of waterlogging is equivalent to total runoff, has usually been used as a simplified way to determine the maximum inundation extent and depth for small and enclosed urban areas such as Longhu District of Shantou city, Longwan District of Wenzhou city, Jing'an District of Shanghai city and Tianjin Binhai New Area (Zhang 1995;Zhao et al 2004Zhao et al , 2010Yin et al 2011c;Hu et al 2012). Based on field survey, GIS point interpolation methods have occasionally been used to obtain the inundation extent and depth for some urban communities (Yin et al 2009;Li et al 2014).…”
Section: Urban Flood Hazard Analysismentioning
confidence: 99%
“…Combined with the distributed hydrologic model, the GIS-based 'water balance' method, which assumes the volume of waterlogging is equivalent to total runoff, has usually been used as a simplified way to determine the maximum inundation extent and depth for small and enclosed urban areas such as Longhu District of Shantou city, Longwan District of Wenzhou city, Jing'an District of Shanghai city and Tianjin Binhai New Area (Zhang 1995;Zhao et al 2004Zhao et al , 2010Yin et al 2011c;Hu et al 2012). Based on field survey, GIS point interpolation methods have occasionally been used to obtain the inundation extent and depth for some urban communities (Yin et al 2009;Li et al 2014). A 2-dimensional (2D) hydrodynamic model (Urban Flood Dynamic Simulation Model -UFDSM) has been generated to simulate urban surface flow around 2000, and then it was improved to represent river/sewer flow in 1D and surface flow in 2D on the basis of unsteady flow theory and unstructured mesh (Qiu et al 2000;Xie et al 2005).…”
Section: Urban Flood Hazard Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The United Nations (2012) reported that flooding has become the most frequent and significant hazard for 633 of the largest cities or urban agglomerations worldwide. Several highly urbanized areas in China, such as Beijing (Gu, Li, Zhou, & Wu, 2013;Li, 2012), Shanghai (Quan et al, 2010;Yin, Yin, Xu, & Wen, 2011), and Guangzhou (Guo & Deng, 2011;Zhang & Ouyang, 2011), have become increasingly prone to flooding in recent years as a result of short-term heavy rains. Thus, immense efforts are focused on improving conventional and innovative stormwater management practices to decrease the runoff volume associated with developed pervious and impervious land covers (Battiata, Collins, Hirschman, & Hoffmann, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Shanghai's urban drainage system has three components: rivers-based drainage system, pipe system, and pumping stations. Up to the present, however, Shanghai's drainage system has only been able to withstand waterlogging by a one-year return period storm-rainfall in the city center and by a half-year return period storm-rainfall in the newly urbanized suburban areas [42,60]. The insufficient drainage system makes urban waterlogging a frequent disaster, which causes widespread damage and disruption to Shanghai [58].…”
Section: Discussionmentioning
confidence: 99%